2022
DOI: 10.3389/fpsyg.2022.946062
|View full text |Cite
|
Sign up to set email alerts
|

Research on the social capital, knowledge quality and product innovation performance of knowledge-intensive firms in China

Abstract: Given the importance of social capital for the success of knowledge-intensive firms (KIFs), scholars have investigated how social capital promotes product innovation through knowledge transfer. However, in contrast to the quantity of transferred knowledge, the role of knowledge quality has been largely ignored. Drawing on the knowledge-based view (KBV) of the firm, this study explores the influences of structural, relational, and cognitive social capital on product innovation and the mediating role of knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…First, by appointing academic personnel in university or institution to the board of directors ( Wolverton and Poch, 2000 ; Compagnucci and Spigarelli, 2020 ), enterprises can receive better internal support and a more streamlined implementation of innovation-related plans and actions due to their professional reputation and influence ( Slaughter and Leslie, 1997 ; Zhou et al, 2022 ). Innovation in technology is long-term and high-risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, by appointing academic personnel in university or institution to the board of directors ( Wolverton and Poch, 2000 ; Compagnucci and Spigarelli, 2020 ), enterprises can receive better internal support and a more streamlined implementation of innovation-related plans and actions due to their professional reputation and influence ( Slaughter and Leslie, 1997 ; Zhou et al, 2022 ). Innovation in technology is long-term and high-risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was indicated that data quality and information quality are often used to assess knowledge quality, and a reliable knowledge quality measure is nonexistent [11]. Zhou et al (2022) explored the impact of knowledge transfer among supply chain members on firm innovation and operational performance, and how knowledge quality affects the relationship between them [18]. Abdollahbeigi and Salehi (2021) found that the quality of knowledge significantly affects the innovation of enterprises, and the ability of innovation will have a significant impact on non-financial performance [19].…”
Section: Knowledge Qualitymentioning
confidence: 99%
“…Ganguly et al (2019) concluded that the transfer of tacit knowledge and the quality of knowledge are positively related to the innovation ability of enterprises [20]. Zhou et al (2022) discovered that the knowledge quality of relational capital and cognitive capital positively affects product innovation performance but structural social capital does not affect the quality of knowledge [18,21]. From these past literatures, it can be found that up to now, no effective assessment method of knowledge quality has been proposed that can assist enterprises to correctly measure the quality of knowledge.…”
Section: Knowledge Qualitymentioning
confidence: 99%
“…Sanchez-Famoso et al [22] found that family and non-family social capital has a combined positive impact on family business innovation. Zhou et al [23] found that corporate social capital indirectly affects product innovation performance through the quality of the transferred knowledge. Zahra [24] concluded that organizing social capital will have a moderating effect on technological capabilities at the international scale.…”
Section: Corporate Social Capitalmentioning
confidence: 99%